Topical glycopyrrolate reduces axillary hyperhidrosis. (13th July 2016) - Baker, D.M.
Abstract: Introduction: Oral anti‐cholinergic medications reduce generalized hyperhidrosis, but the effectiveness of topical anticholinergic solutions on axillary hyperhidrosis is unclear. This study determines the initial effectiveness of 1% and 2% topical glycopyrrolate spray and compares this with Botulinum toxin type A injections for the management of axillary hyperhidrosis. Methods: In a non‐randomized, consecutive patient, prospective questionnaire, treatment comparison study, 40 patients with axillary hyperhidrosis were allocated to one of four study groups (10 patients to each group): (a) 1% glycopyrrolate spray, (b) 2% glycopyrrolate spray, (c) subcutaneous Botulinum toxin type A injections, (d) no treatment. Clinical outcomes were measured by comparing a prospectively administered questionnaire, completed both pre‐treatment and 6 weeks after starting treatment. Forty healthy volunteers without axillary hyperhidrosis completed the same questionnaire. Results: The three treatment groups showed a significant ( P < 0.05) improvement in their hyperhidrosis scores following treatment. The degree of improvement was less for the 1% glycopyrrolate group when compared with the Botulinum toxin type A group ( P < 0.05), but there was no difference in treatment outcomes between the 2% glycopyrrolate and Botulinum toxin type A groups. No treatment group experienced reduced hyperhidrosis to a level similar to those without hyperhidrosis. Patients in both, the 2% glycopyrrolate and Botulinum toxin type A groups reported a significant improvement in axillary hyperhidrosis symptoms. These included reduction in psychologically precipitating factors (e.g. public speaking) and axillary hyperhidrosis‐specific physical effects (e.g. limitation of clothing choice). Conclusions: Topical glycopyrrolate spray could provide a further treatment modality to manage axillary hyperhidrosis.